Proyeksi Produksi Dan Konsumsi Kedelai Indonesia - Aldillah, Rizma (Jurnal Ekonomi Kuantitatif Terapan, 2015)
Due to the higher growth in consumption of soybean is higher than that of it’s production, the domestic consumption has to be fullfilled from imports. FAO data show that, the rate of import of soybean on average is 200 percent in the last 52 years, which show that until now self-sufficiency in soybean has not been achieved. To see whether Indonesia can reach self-sufficient in soybeans in the future, some forecast studies analized. Purpose of this study are: (1) growth analysis of soybean production and consumption, (2) response analysis of soybean area harvested and yield. The results ofthe analysisconcludedis that theproductionin 2020increase by 6.80% per annum, andconsumptionis increase by 2.10% per annum, butis predicted to the balancestillshowsa deficit, the deficitshoweda decreaseby 0.98% per annum.  The results of analysis show indication that it would be growth of soybean area in the future, which showed by the average production growth of approximately 3 times more than the average consumption growth.The implications and findings from this researchthat Indonesia has the opportunity to purpose its soybeans self-sufficient in the future.
Keywords: consumption; forecast; production; self-sufficient; soybeans